Comparison of surgical outcomes of tympanoplasty assisted by conventional microscopic method and endoscopic method - Shoeb, Mohammed; Gite, Vinod; Bhargava, Samir; Mhashal, Shashikant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: The introduction of the operating microscope has significantly enhanced the outcome of tympanoplasty by improving the accuracy of the technique. The operating microscopy provides a magnified image in straight line; hence the surgeon can’t visualize the deep recesses of the middle ear in single operating field. This is overcome by use of rigid endoscope for tympanoplasty. In rigid endoscopy view is better but surgeons 2 hands are not free so manipulation here is difficult. Methods: 30 cases of safe CSOM from each group viz microscopic assisted (MES) & endoscopic assisted (EES) were selected operated by full cuff (superiorly based tympanomeatal flap technique) and compared for graft uptake, hearing improvement & complications. Results: Graft uptake rate was 93.33% in both groups. In our study the pre operative mean air bone gap of the patients was 37.23+5.79 db after surgery at 6 months came down to 17.17+3.31 db hence after calculating the mean air bone gap closure it came down to be 20.4+4.85. Which showed a significant improvement in the hearing (p value 1.493E-23 which is less than 0.05). 6.67% cases from both groups showed failure of graft uptake. Conclusions: The graft uptake, hearing improvement, Complications produced by each of the techniques in large, subtotal, and anterior moderate perforations by each technique is comparable i.e. both techniques have same results.